2011
DOI: 10.1099/mic.0.040436-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DRA0282 from Deinococcus radiodurans for its role in bacterial resistance to DNA damage

Abstract: DRA0282, a hypothetical protein, was found in a pool of nucleotide-binding proteins in Deinococcus radiodurans cells recovering from gamma radiation stress. This pool exhibited an unusual inhibition of nuclease activity by ATP. The N terminus of DRA0282 showed similarity to human Ku80 homologues, while the C terminus showed no similarities to known proteins. The recombinant protein required Mn 2+ for its interaction with DNA and protected dsDNA from exonuclease III degradation. The binding of the protein to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Also, in vitro binding studies with circular single-stranded DNA and DNA containing hairpin loops at both ends demonstrated that eukaryotic Ku could bind to a 'closed' substrate lacking free ends with no significant difference in binding affinity compared with DNA with free ends [27,29]. Recently, a homologue of eukaryotic Ku from Deinococcus radiodurans was shown to bind supercoiled DNA with 67-fold higher affinity as compared with linear DNA, also supporting the notion that DNA binding by Ku is probably more complex than originally thought, and consistent with the possibility that Ku may associate with local secondary structures [30]. Furthermore, we recently demonstrated that the lysine-rich C-terminal repeats of M. smegmatis Ku confer on the protein the ability to promote DNA end-joining, consistent with its role in NHEJ [10].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Also, in vitro binding studies with circular single-stranded DNA and DNA containing hairpin loops at both ends demonstrated that eukaryotic Ku could bind to a 'closed' substrate lacking free ends with no significant difference in binding affinity compared with DNA with free ends [27,29]. Recently, a homologue of eukaryotic Ku from Deinococcus radiodurans was shown to bind supercoiled DNA with 67-fold higher affinity as compared with linear DNA, also supporting the notion that DNA binding by Ku is probably more complex than originally thought, and consistent with the possibility that Ku may associate with local secondary structures [30]. Furthermore, we recently demonstrated that the lysine-rich C-terminal repeats of M. smegmatis Ku confer on the protein the ability to promote DNA end-joining, consistent with its role in NHEJ [10].…”
Section: Introductionsupporting
confidence: 62%
“…The crystal structure of human Ku shows that it has a tripartite organization consisting of an N-terminal α/β von Willebrand factor A domain, a central βbarrel domain and a subunit-specific C-terminal SAP domain that together form a pseudosymmetrical ring-like channel that can accommodate a DNA duplex [9]. In contrast, the prokaryotic Ku proteins are homodimers [1,4,5] and much smaller (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), consisting of the conserved central 'ring-shaped' core domain of eukaryotic Ku and lacking the N-and C-terminal domains present in Ku70/80, except for homologues from a few bacteria such as Streptomyces coelicolor that contain a SAP-like domain [1,4,5]. Also, Ku proteins from free-living mycobacterial species found in soil and natural reservoirs contain at their C-terminus low complexity repeats containing the amino acids lysine, alanine, and proline that promote DNA end-joining [10].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of bound fraction of DNA was plot-ted against protein concentration using GraphPad Prism version 5. The K d for curve fitting of individual plots was determined by the software working on the principle of the least squares method, applying the formula, Y ϭ B max ϫ [X]/K d ϩ [X], where [X] is the protein concentration, and Y is the bound fraction as described earlier (43). To determine the log equilibrium dissociation constant (log K i ) of nonphosphorylated and phosphorylated DrRecA, the competition assay was performed, where the binding of 0.2 pmol of ssDNA/dsDNA was challenged with either unlabeled homologous ssDNA and dsDNA (2.5-40 M) or unlabeled heterologous dsDNA and ssDNA (2.5-40 M), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The consensus boxes similar to the typical P1 element were identified by using Bioedit, version 7, software. The functional motif search was carried out by using standard online bioinformatics tools, as reported previously (10). In brief, the amino acid sequences of DR_0012 and DR_0013, annotated as putative ParB and ParA proteins, respectively, on chromosome I of this bacterium were subjected to a PSI-BLAST search with the Swiss-Prot database, with "genome partitioning proteins" as key words.…”
Section: Methodsmentioning
confidence: 99%
“…, where [X] is the protein concentration, Y is the bound fraction, and B max is the maximum binding capacity, as described previously (10).…”
Section: Expression and Purification Of Recombinant Parb1 And Para1mentioning
confidence: 99%